Research Methodology Training for Middle School Teachers to Improve the Quality of Educational Research Proposals - Eka Murtinugraha; Shilmi Arifah (Universitas Negeri Makassar, 2023)
To become a professional teacher writing and publishing scientific papers is important. Most teachers consider that research is not an obligation that needs to be done and is considered a difficult thing. So that this community service activity is focused on improving the skills of teachers in compiling and publishing educational research through research methodology training. The activity was carried out at Vocational Education (VE) of Yayasan Pendidikan Islam Nurul Huda followed by 2 lecturers as presenters and 31 teachers. The training activities consist of 3 stages, namely preparation, implementation, and evaluation of training. The results of the evaluation of activities through the distribution of pre-test and post-test questionnaires obtained the ability of teachers in the knowledge of preparation of teaching materials by 69.677% and 88.226%, so there was an increase of 18.548%. Based on the sample paired t-test, the value of Sig. (2-tailed) ρ-value is 0.000. So, training activities are very effective in improving the competence in preparing research proposals for VE teachers. This shows that there is an increase in the preparation of educational research proposals through research methodology training for teachers in VE. This activity is beneficial because, in addition to adding skills, this activity is an update of knowledge and experience.